2015
DOI: 10.1073/pnas.1424954112
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy confers resistance to siderophore-mediated killing by Pseudomonas aeruginosa

Abstract: In the arms race of bacterial pathogenesis, bacteria produce an array of toxins and virulence factors that disrupt core host processes. Hosts mitigate the ensuing damage by responding with immune countermeasures. The iron-binding siderophore pyoverdin is a key virulence mediator of the human pathogen Pseudomonas aeruginosa, but its pathogenic mechanism has not been established. Here we demonstrate that pyoverdin enters Caenorhabditis elegans and that it is sufficient to mediate host killing. Moreover, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
207
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(217 citation statements)
references
References 38 publications
10
207
0
Order By: Relevance
“…It has previously been shown that selection for nonproducers is expected to lower bacterial virulence (65,66). We observed that highly resistant producers also arose in mixed cultures, but they were outcompeted by resistant nonproducers.…”
Section: Discussionmentioning
confidence: 60%
“…It has previously been shown that selection for nonproducers is expected to lower bacterial virulence (65,66). We observed that highly resistant producers also arose in mixed cultures, but they were outcompeted by resistant nonproducers.…”
Section: Discussionmentioning
confidence: 60%
“…Interestingly, while we were working on this paper, it was shown that iron chelators can induce mitophagy in mammalian cells [48] and in C. elegans [49], possibly as a way of recycling iron from the mitochondrial storage. These findings insinuate that, although frataxin silencing can induce mitophagy via cytosolic iron deprivation, the non-additive effects of the two combined treatments could also be a consequence of iron depletion-induced mitochondrial damage.…”
Section: Discussionmentioning
confidence: 96%
“…67 However, Phen is unable to exert similar effects in neuronal-like SH-SY5Y cells, suggesting that its mitophagic activity might be cell type dependent. 68 In addition, the structurally similar siderophore 2'2-bipyridyl was shown to extend lifespan in C. elegans by inducing a mitophagic response that was dependent on PINK1 as well as PBR-1 and DCT-1, the C. elegans homologues of Parkin and NIX1/BNIP3 respectively ( Table 1 and Figure 5b).…”
Section: Iron Chelatorsmentioning
confidence: 99%